AKTIVITAS PENGURUS HIMSOS DALAM MELAKSANAKAN PROGRAM KERJA DI PRODI PENDIDIKAN SOSIOLOGI FKIP UNTAN PONTIANAK - Kurniasari, Riski; Salim, Izhar; Rosyid, Rum (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractÂ This study aimed to determine the activities of the Sociology Education Student Association management in implementing the work program of the Sociology Education Study Program, Teacher Training and Education Faculty of Tanjungpura University Pontianak, the period of 2018/2019. Qualitative research with descriptive method was used in this study. The subject of the research was the management of the student association. The techniques of data collection used were observation, interview, and documentation, as well as the guides for observation and interview, and the documentation tools were used as the tools of data collection. Data analysis was presented in descriptive qualitative form with 3 informants consisting of the chair, secretary, and treasurer of the student association. The results showed that the activities in implementing the work program consist of planning, manifested in goals setting and formulation in the strategy of achieving the goals; organizing, consisting of structuring and recruitment; implementation, consisting of building cooperation and developing skills and creativity; and supervising, consisting of monitoring and evaluation of the work programs of the student association.Â Keywords: Activities, Management, Organization, Work Program